Identifikasi Gaya Belajar Visual, Auditori, Dan Kinestetik Pada Peserta Didik Sekolah Dasar - Ediyanto Ediyanto (Student Research Journal, 2023)
This study aims to identify the visual, auditory, and kinesthetic learning styles of elementary school students. The study uses a qualitative method with a descriptive approach. The data collection technique used is by distributing instruments containing questions that can identify visual, auditory, and kinesthetic learning styles. The questions are given to elementary school students with a choice of yes or no as the answer. The data analysis technique used is by conducting a descriptive analysis of the answers given by the students. The findings of this study indicate that visual and kinesthetic learning styles are dominant in elementary school students. Auditory learning style has a relatively low dominance. This shows that teachers must pay attention to students' learning styles in the learning process to make it more effective and efficient.